206 High Resolution Ultrasound for Evaluation of Peripheral Nerve Injuries: Retrospective Examination of an Emerging Technology. (April 2023) - Xiao, Tianqi; Herring, Eric; Azghadi, Adel; Labak, Collin; Preston, David; Miller, Jonathan
Abstract : INTRODUCTION: Recovery from peripheral nervous system injury (PNI) after trauma has been shown to improve with earlier detection and treatment. Unfortunately, surgical treatments are usually postponed several months after injury due to the need to evaluate for potential recovery without intervention. If diagnostic modalities are able to identify which nerve injuries will require surgical intervention sooner, we may be able to significantly improve outcomes after peripheral nerve injury. High-resolution ultrasound (HRUS) is an imaging modality that potentially could provide this in an economic manner. METHODS: A retrospective chart review was conducted for all patients who received an HRUS of their PNI at our institution from 01/01/2020-01/31/2022. RESULTS: A total of 32 patients were included. The mean age was 45 years with a male predominance (69%). Neuronal and surrounding tissue pathology greater than or equal to the fascicular level could be identified with HRUS. EDx studies were available for 28 (88%) and clinical exams were available for 32 (100%) of patients. Comparing HRUS to the gold standard of a combination of clinical exam and EMG findings, HRUS had a sensitivity of 94% at identifying PNI. Ultimately, 19 (59%) of patients evaluated using HRUS underwent operative intervention. CONCLUSIONS: HRUS is an important emerging imaging modality that can identify and characterize PNI. Our study demonstrates the high sensitivity of HRUS in detecting PNI. Additionally, HRUS in our study identified a number of features that may serve as surrogate markers of injury useful in prognosticating recovery. Further work is needed to define the earliest time point HRUS can be used to identify a PNI.